Surface roughness analysis of beryllium-copper alloy in micro end milling - Mehfuz, R.; Ali, Mohammad Yeakub (2007)
In this paper, the effect of feed per tooth and depth of cut during micro end milling of beryllium-copper alloy, a mold material, has been analyzed. Central composite design, a response surface method, was used to statistically analyze the influence of these process parameters on the surface roughness. The interaction effect of parameters was also discussed. Statistical models for micro-end-milling were established to predict the average (Ra), maximum (Ry) and ten-point (Rz) surface roughness. Ra was found strongly influenced by feed while, Ry was influenced by the interaction effects of feed and depth of cut. Rz was influenced by both feed and the interaction of feed and depth of cut. Surface roughness in the range of 0.10 - 0.20 μm was observed.